2014
DOI: 10.4103/1658-354x.136432
|View full text |Cite
|
Sign up to set email alerts
|

Hip hemiarthroplasty using major lower limb nerve blocks: A preliminary report of a case series

Abstract: Background:Major lower limb nerve blocks are relatively safe techniques. However, their efficacy for hip hemiarthroplasty is unknown. The objective of this study was to determine the effectiveness of combined femoral, sciatic, obturator and lateral femoral cutaneous (LFC) nerve blocks in providing adequate anesthesia for hip hemiarthroplasty.Materials and Methods:A total of 20 patients with fracture neck femur; who underwent hip hemiarthroplasty, participated in this observational study. In the induction room,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Performance of multiple nerve blocks requires large doses of bupivacaine so we have to be alert about the risk of LA toxicity which causes convulsions at plasma level 4 μg/ml. For this reason, enantiomer LA with lower concentration has to be used [15] and we found that it theoretically provides adequate anaesthesia for this type of surgical procedure. Some studies aimed to reducing the number of nerves blocked to decrease the risk of toxicity but it may cause inadequate anaesthesia to perform the required surgical procedures [16].…”
Section: Discussionmentioning
confidence: 99%
“…Performance of multiple nerve blocks requires large doses of bupivacaine so we have to be alert about the risk of LA toxicity which causes convulsions at plasma level 4 μg/ml. For this reason, enantiomer LA with lower concentration has to be used [15] and we found that it theoretically provides adequate anaesthesia for this type of surgical procedure. Some studies aimed to reducing the number of nerves blocked to decrease the risk of toxicity but it may cause inadequate anaesthesia to perform the required surgical procedures [16].…”
Section: Discussionmentioning
confidence: 99%
“…Performance of multiple nerve blocks requires large doses of bupivacaine so we have to be alert about the risk of LA toxicity which causes convulsions at plasma level 4 µg/ml. For this reason, enantiomer LA with lower concentration has to be used [15] and we found that it theoretically provides adequate anaesthesia for this type of surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Because all other branches of the sacral plexus can be blocked, it is more effective for hip surgery when combined with lumbar plexus block. However, due to the lack of reliable sensory block in dermatome T12 and L1 [ 25 ], a combination of lumbar plexus and sacral plexus block failed to provide consistent surgical anesthesia for hip surgery [ 6 , 8 , 26 , 27 ]. Several techniques have been introduced to overcome the limitation, such as large dosage of propofol and opioids [ 8 ], infiltration at incision [ 4 ] and iliac crest point block [ 9 ].…”
Section: Discussionmentioning
confidence: 99%